The role of defects in the structural and photocatalytic properties of Mg/B co-doped ZnO nanoparticles - ŞENGÜL, MUSTAFA TAYLAN; TAV, CUMALİ; YAHŞİ, UĞUR (My University, 2023)
Mg/B co-doped ZnO nanoparticles were synthesized by using the sol–gel technique to investigate the role of the defects on the structural, biological and photocatalytic properties. Single phases with ZnO wurtzite hexagonal structures were observed in the X-ray diffraction measurements. Scanning electron microscopy and transmission electron microscopy were used to determine the surface, particle size, and shapes of the nanoparticles. Electron dispersive spectroscopy was used to determine the elemental compositions of the nanoparticles. Photoluminescence spectrophotometry and positron annihilation lifetime spectroscopy were used to study the defect type, density and crystal quality of Mg/B co-doped ZnO nanoparticles. A broad visible emission band (including violet–blue-orange and red emissions) was observed. The violet–blue-orange and red emissions could be attributed to the O vacancies (VO), interstitial Zn (Zni), Zn vacancies (VZn), and the double charged oxygen vacancy (VO(++)), which were strongly dependent on the synthesis conditions and doping ratio. SEM images revealed that Mg/B-co-doped ZnO nanoparticle magnifications were dense, quasispherical, and agglomerating. The photocatalytic activities and blood compatibilities of Mg/B co-doped ZnO nanoparticles were studied by the photocatalytic degradation tests of crystal violet (CV) and hemolysis tests, respectively.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Fizik; Atom ve Molekül Fiziği; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Temel Bilimler; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Signal Processing; Physics; Atomic and Molecular Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; FİZİK, YOĞUN MADDE; FİZİK, ATOMİK, MOLEKÜLER VE KİMYASAL; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; PHYSICS; ENGINEERING, ELECTRICAL & ELECTRONIC; PHYSICS, CONDENSED MATTER; PHYSICS, ATOMIC, MOLECULAR & CHEMICAL; Elektronik, Optik ve Manyetik Malzemeler; Fizik Bilimleri; Atom ve Moleküler Fizik ve Optik; Yoğun Madde Fiziği; Elektrik ve Elektronik Mühendisliği; Electronic, Optical and Magnetic Materials; Physical Sciences; Atomic and Molecular Physics, and Optics; Condensed Matter Physics; Electrical and Electronic Engineering